Using the right to veto in the United Nations Security Council. - طيبا سحر (Latakia University Journal - Economic and Legal Sciences Series, 2025)
This research examines a topic considered one of the most important contemporary issues for all countries worldwide. The topic is the veto power on decisions of the United Nations Security Council, granted to the five permanent member states. According to this power, the objection of any of these five states is enough to reject a decision without giving any reasons. In reality, the use of this right carries negative consequences, as it has become a means of interfering in the affairs of countries on one hand, and a means of obstructing the implementation of international decisions condemning a state’s aggression against another state, and avoiding these decisions on the other hand. This constitutes a direct violation of international law and the Charter of the United Nations itself. The research will address the following main topics: an introduction to the United Nations Security Council, including its establishment, composition, powers, and working methods, as well as its subsidiary bodies and voting procedures. The second topic will define the veto power and its international perception, identify some of the problems it raises within the United Nations Security Council, and finally, present some proposals that could help mitigate the negative aspects of exercising this right.